Engineered Sensory Nerve Guides Self‐Adaptive Bone Healing via NGF‐TrkA Signaling Pathway. Issue 10 (1st February 2023) - Zhang, Zengjie; Wang, Fangqian; Huang, Xin; Sun, Hangxiang; Xu, Jianxiang; Qu, Hao; Yan, Xiaobo; Shi, Wei; Teng, Wangsiyuan; Jin, Xiaoqiang; Shao, Zhenxuan; Zhang, Yongxing; et al.
Abstract: The upstream role of sensory innervation during bone homeostasis is widely underestimated in bone repairing strategies. Herein, a neuromodulation approach is proposed to orchestrate bone defect healing by constructing engineered sensory nerves (eSN) in situ to leverage the adaptation feature of SN during tissue formation. NGF liberated from ECM‐constructed eSN effectively promotes sensory neuron differentiation and enhances CGRP secretion, which lead to improved RAOECs mobility and osteogenic differentiation of BMSC. In turn, such eSN effectively drives ossification in vivo via NGF‐TrkA signaling pathway, which substantially accelerates critical size bone defect healing. More importantly, eSN also adaptively suppresses excessive bone formation and promotes bone remodeling by activating osteoclasts via CGRP‐dependent mechanism when combined with BMP‐2 delivery, which ingeniously alleviates side effects of BMP‐2. In sum, this eSN approach offers a valuable avenue to harness the adaptive role of neural system to optimize bone homeostasis under various clinical scenario. Abstract : The adaptation feature of sensory nerve during tissue formation is leveraged to propose a neuromodulation approach to orchestrate bone defect healing by constructing engineered sensory nerves (eSN) in situ. eSN sustained‐release NGF to promote sensory nerve reinnervation, which regulates MSC osteogenic differentiation, vascular regeneration, and regulates osteoblast and osteoclasts to participate in bone remodeling and guides self‐adaptive bone healing.